Multiscale Approach to Shock to Detonation Transition in Energetic Materials. Issue 2 (11th November 2019) - Jackson, Thomas L.; Zhang, Ju; Short, Mark
Abstract: In this work we present a multiscale approach for coupling the dynamics of void collapse at the microscale to simulations at the mesoscale. We solve the reactive Euler equations, with the energy equation augmented by a power deposition term. The reaction rate at the mesoscale is modelled using a pressure‐dependent power law. The deposition term is based on previous simulations of void collapse, modelled at the mesoscale as hot‐spots. The equation of state was previously calibrated for PBX 9501. The run‐to‐detonation distance is calculated as part of the numerical solution procedure. Results for 1‐D, 2‐D homogeneous, and 2‐D heterogeneous medium are presented, and show good agreement to experimental data. Abstract :